KAJIAN TENTANG WANITA DAN PERUBAHAN PERDESAAN - Istiana Hermawati (Sosio Informa, 2003)
Studies on Women Issues and Social Change in Rural Areas.Absctract Green revolution and industrialization in villages that being discourse of developmentin order ORBA, proven already replace and marginalized women in village from their economicand social function. Because of that, their poor life become very poor, full of problems andsucceptible for domination of man and another external force in system and stucture of social,economic, politic and culture was growth in village. That is discribe gender inequality in publicpolicy by government. Because of that, very important to make positive restructurization forsocial position of women in village through asistance program as technology asistant that relevant, to lighten their load work, and education and training for the operasionalization. Assistance for women villages by Government Organization (GO) and Non Government Organization (NGO) so it can insure women rights, developed their capacity with maximize, so their aspiration and perseption can accomodation and making of colour for development. So with that effort, in role and function of women will be increase and because of it, their participation in development also become large. With another word, development consider aspects and interest of women then gender distortion and inequality in development would be avoided and minimized.Kata Kunci: Perubahan perdesaan, diskriminasi, revolusi hijau